Exploring English Self-Efficacy Among Vietnamese Undergraduates: The Role of Gender and Academic Major - Ngoc Tran, Huy; Duc Tran, Trong; Doan Ngoc Nguyen, Thuong; Thi Ngoc Nguyen, Mai; Xuan Tran, Quynh (Center of Language Development, Institut Agama Islam Negeri Madura, 2025)
Self-efficacy has been shown to be a key determinant of foreign language learners' efforts and academic achievement. Hence, understanding learners' self-efficacy and the factors that may influence it is vital to improving learners' language learning outcomes. This study investigated Vietnamese learners' overall English self-efficacy and explored potential differences by academic major and gender, using a cross-sectional, quantitative design. 549 participants from four majors at a university in Vietnam were recruited through non-proportional quota sampling. The results revealed that the participants generally have moderate English self-efficacy, with the highest self-efficacy reported in reading. There was a significant difference between majors, as English majors showed higher self-efficacy than their non-major counterparts. In terms of gender, male learners are found to have higher English self-efficacy than female learners, although the gender difference was modest. These findings highlight the importance of structured training, underscoring the need for new pedagogical strategies to boost English learners' self-efficacy and providing implications for further research.